Pengembangan Boardgame Edukasi "Virus-Board" Sebagai Media Pembelajaran Biologi pada Materi Virus Kelas X SMA - Iftitakhul Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Biology is one of the subjects taught at the senior high school level that focuses on the study of living organisms. Biological topics often involve complex life concepts and numerous Latin terms that are difficult for students to understand. One topic that is interesting yet considered challenging in biology is viruses. The topic of viruses encompasses complex concepts such as structure, replication, roles, and interactions between viruses and their host cells. Many students experience difficulties in distinguishing viruses from other living organisms, particularly because viruses are unable to reproduce independently. Therefore, to support students’ understanding of virus-related concepts, it is necessary to develop an up-to-date learning medium in the form of an educational board game. This study aims to determine the validity and practicality of the educational board game learning media “Virus-Board” as a biology learning medium on virus material, as well as students’ perceptions of the board game based learning media. The research employed a research and development (R&D) method using the ADDIE development model. The results of the validity test of the educational board game learning media “Virus-Board”, as assessed by expert validators, showed an analysis result of 90.12%. This result falls into the “very valid” category, indicating that the learning media is suitable for use in classroom learning. The practicality test of the educational board game learning media “Virus-Board” yielded an analysis result of 90.38%, while the quantitative data analysis of students’ perceptions of the developed educational board game learning media “Virus-Board” on virus material obtained an average score of 90.23%. These results fall into the “very interesting” category, indicating that students’ perceptions of the implementation of the educational board game learning media “Virus-Board” on virus material are highly positive.
:: Finalisasi Repositori File 6 Juni 2026_Kurnadi
Keywords: Boardgame; Validity and practicality; Perception